Retrospective Evaluation of Sedation Techniques for Tooth Extraction in Paediatric Patients - Mridul Sharma; Amit K. Sahu; Puja Kaila; Ali Abdel H. A. A. Hassan; Mohamed Mansy; Raksha Thakur; Husham E. Homeida (Journal of Pharmacy and Bioallied Sciences)
Background: Dental procedures often require local anesthesia, but managing fearful patients, especially children, can be challenging, potentially leading to dental phobia development. Sedation methods such as conscious sedation, deep sedation, or general anesthesia can aid in managing these patients. Material and Method: This study focuses on evaluating various sedation techniques used in an Oral and Maxillofacial Surgery Clinic for adults with special needs requiring dental treatments under sedation or general anesthesia. A retrospective analysis was conducted on 250 adult patients with special needs who underwent dental procedures between January 2019 and December 2023. Data on demographic characteristics, types of procedures, sedation techniques used, dosages, and complications were collected from medical records. Sedation techniques included midazolam-sufentanil, ketamine-midazolam, oral midazolam, chloral hydrate, ketamine, and propofol. Results: The midazolam-sufentanil combination was the most commonly used sedation technique (27.2%), followed by ketamine-midazolam (21.6%). Complications such as respiratory issues (2.9%), cardiovascular events (1.5%), nausea/vomiting (4.4%), and prolonged recovery time (2.9%) were observed. Conclusion: Overall, the incidence of complications was relatively low, indicating the safety and efficacy of the sedation techniques. Sedation techniques, particularly the midazolam-sufentanil and ketamine-midazolam combinations, were found to be effective and safe for managing dental procedures in adults with special needs. Personalized sedation approaches based on individual patient factors are essential for optimizing outcomes. Further research is needed to explore long-term effects and patient satisfaction.